OROGENIC GOLD DEPOSITS: A PROPOSED CLASSIFICATION IN THE CONTEXT OF THEIR CRUSTAL DISTRIBUTION AND RELATIONSHIP TO OTHER GOLD DEPOSIT TYPES - Groves D.I.; Gebre-Mariam M.; Hagemann S.G.; Goldfarb R.J.; Robert F. (My University, 1998)
The so-called `mesothermal' gold deposits are associated with regionally metamorphosed terranes of all ages. Ores were formed during compressional to transpressional deformation processes at convergent plate margins in accretionary and collisional orogens. In both types of orogen, hydrated marine sedimentary and volcanic rocks have been added to continental margins during tens to some 100 million years of collision. Subduction-related thermal events, episodically raising geothermal gradients within the hydrated accretionary sequences, initiate and drive long-distance hydrothermal fluid migration. The resulting gold-bearing quartz veins are emplaced over a unique depth range for hydrothermal ore deposits, with gold deposition from 15–20 km to the near surface environment.On the basis of this broad depth range of formation, the term `mesothermal' is not applicable to this deposit type as a whole. Instead, the unique temporal and spatial association of this deposit type with orogeny means that the vein systems are best termed orogenic gold deposits. Most ores are post-orogenic with respect to tectonism of their immediate host rocks, but are simultaneously syn-orogenic with respect to ongoing deep-crustal, subduction-related thermal processes and the prefix orogenic satisfies both these conditions. On the basis of their depth of formation, the orogenic deposits are best subdivided into epizonal (<6 km), mesozonal (6–12 km) and hypozonal (>12 km) classes.